Recent Strategies in Non-Heme-Type Metal Complex-Catalyzed Site-, Chemo-, and Enantioselective C–H Oxygenations - Doiuchi, Daiki; Uchida, Tatsuya (Synthesis, 2021)
C–H bonds are ubiquitous and abundant in organic molecules. If such C–H bonds can be converted into the desired functional groups in a site-, chemo-, diastereo-, and enantio-selective manner, the functionalization of C–H bonds would be an efficient tool for step-, atom- and redox-economic organic synthesis. C–H oxidation, as a typical C–H functionalization, affords hydroxy and carbonyl groups, which are key functional groups in organic synthesis and biological chemistry, directly. Recently, significant developments have been made using non-heme-type transition-metal catalysts. Oxygen functional groups can be introduced to not only simple hydrocarbons but also complex natural products. In this paper, recent developments over the last fourteen years in non-heme-type complex-catalyzed C–H oxidations are reviewed.1 Introduction2 Regio- and Chemo-Selective C–H Oxidations2.1 Tertiary Site-Selective C–H Oxidations2.2 Secondary Site-Selective C–H Oxidations2.3 C–H Oxidations of N-Containing Molecules2.4 C–H Oxidations of Carboxylic Acids2.5 Chemo- and Site-Selective Methylenic C–H Hydroxylations3 Enantioselective C–H Oxidations3.1 Desymmetrizations through C–H Oxidations3.2 Enantiotopic Methylenic C–H Oxygenations4 Conclusion
Keywords: C–H oxidation; non-heme-type catalyst; site-selectivity; chemoselectivity; enantioselectivity; oxygen atom transfer